Kindergarten Class Graduation at Jackson Elementary School - Watkins, Howard::::::::: (1984)
Teacher Leanne Wiens with Devon Bleile-Kratzer, Andrew Pitcher, Adam Watkins, Ramon Andrade and one other classmate receiving Certificates of Achievement Awards Adam's Adam for Scholarship and Citizenship